2008
DOI: 10.1152/physiolgenomics.00265.2007
|View full text |Cite
|
Sign up to set email alerts
|

Human cardiac-specific cDNA array for idiopathic dilated cardiomyopathy: sex-related differences

Abstract: Idiopathic dilated cardiomyopathy (IDCM) constitutes a large portion of patients with heart failure of unknown etiology. Up to 50% of all transplant recipients carry this clinical diagnosis. Female-specific gene expression in IDCM has not been explored. We report sex-related differences in the gene expression profile of ventricular myocardium from patients undergoing cardiac transplantation. We produced and sequenced subtractive cDNA libraries, using human left ventricular myocardium obtained from male transpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 70 publications
0
39
1
Order By: Relevance
“…Intriguingly, Haddad et al reported sex-related differences in the gene expression profile of the failing myocardium. 65 They found deregulation of genes involved in energy metabolism and regulation of those related to transcription and translation in the failing myocardium of female patients with DCM, whereas genes related to muscle contraction were deregulated in the failing myocardium of male patients.…”
Section: Sex-specific Gene Expressionmentioning
confidence: 98%
See 1 more Smart Citation
“…Intriguingly, Haddad et al reported sex-related differences in the gene expression profile of the failing myocardium. 65 They found deregulation of genes involved in energy metabolism and regulation of those related to transcription and translation in the failing myocardium of female patients with DCM, whereas genes related to muscle contraction were deregulated in the failing myocardium of male patients.…”
Section: Sex-specific Gene Expressionmentioning
confidence: 98%
“…They have usually compared gene expression between opposing pairs of samples, such as non-failing vs failing hearts, [53][54][55][56][57][58][59] ischemic vs non-ischemic hearts, 53,60 hypertrophic vs failing hearts, 61 atria vs ventricles 62 or male vs female failing hearts. 65 Gene Expression Profile of DCM Yang et al 53 performed microarray analysis of 4 human myocardial samples harvested from 2 patients without HF, 1 patient with DCM and 1 patient with ischemic cardiomyopathy (ICM) using the Affymetrix Hu6800 GeneChip microarray. They reported 12 genes with altered expression in both failing hearts compared with the normal hearts and 5 genes that were only detectable in the failing hearts.…”
Section: Microarray Analysis Of the Failing Myocardiummentioning
confidence: 99%
“…30 Gene expression profiling in end-stage failing human hearts has revealed similar sex differences as found in animals with HF: less downregulation of energy metabolism in female hearts and more matrix induction in male hearts. 31 …”
Section: Human Hearts: Sex Differences In Pathological Mhmentioning
confidence: 99%
“…Nieminen et al (27) evaluated sex differences in patients hospitalized for acute heart failure in the EuroHeart Failure Survey II and found that men had DCM more frequently than women. Likewise, Haddad et al (13) reported that men with idiopathic DCM undergoing transplantation showed a different gene expression profile than women. Thus the EP4 KO model, with its sexual dimorphism in DCM, may represent a good model to understand the molecular basis of sex differences in disease progression.…”
Section: Sex Differences and Dcmmentioning
confidence: 99%